2015
DOI: 10.3846/13923730.2014.890657
|View full text |Cite|
|
Sign up to set email alerts
|

An Early Cost Estimation Model for Hydroelectric Power Plant Projects Using Neural Networks and Multiple Regression Analysis

Abstract: Energy is increasingly becoming more important in today's world, whereas energy sources are drastically decreasing. One of the most valuable energy sources is hydro energy. Because of limited energy sources and excessive energy usage, cost of energy is rising. Among the electricity generation units, hydroelectric power plants are very important, since they are renewable energy sources and they have no fuel cost. To decide whether a hydroelectric power plant investment is feasible or not, project cost and amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(23 reference statements)
1
17
0
Order By: Relevance
“…Similarly, Shehab et al (2010) concluded that the ANN developed for water projects cost prediction produced much more accurate results compared to the regression one and thus demonstrated superior capabilities in mapping relationships between inputs and outputs in limited data environments. Gunduz and Bayram Sahin (2015) also confirmed in their research that the ANN that was trained on cost data from 41 hydroelectric power plant projects had substantially higher prediction accuracy than the respective regression model developed. Similar performance superiority of the ANNs over linear regression has also been reported by Creese and Li (1995) for their timber bridge cost prediction model.…”
Section: Literature Reviewmentioning
confidence: 70%
See 2 more Smart Citations
“…Similarly, Shehab et al (2010) concluded that the ANN developed for water projects cost prediction produced much more accurate results compared to the regression one and thus demonstrated superior capabilities in mapping relationships between inputs and outputs in limited data environments. Gunduz and Bayram Sahin (2015) also confirmed in their research that the ANN that was trained on cost data from 41 hydroelectric power plant projects had substantially higher prediction accuracy than the respective regression model developed. Similar performance superiority of the ANNs over linear regression has also been reported by Creese and Li (1995) for their timber bridge cost prediction model.…”
Section: Literature Reviewmentioning
confidence: 70%
“…However, the validation error is not a good estimate of the generalization error, and thus, a third set of data, not used during the (Gunduz & Sahin, 2015) has also been highlighted. Other applications of ANNs include financial tools, electric load consumption prediction and intelligent manufacturing systems (Huang & Zhang 1994, Zhang, Patuwo & Hu (1998.…”
Section: Cost Prediction At Early Design Stages: Challenges and Methomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, [15] have investigated forecasting hydroelectric power plant project's cost via ANN through which, three different architectures have been generated and examined, while seeking the best performance. The results have been compared with those of RA and concluded that the ANN shows better promising results.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, RA can be classified as a data oriented technique that deals with just the data in hand and not the characteristics behind them and is divided to two linear and nonlinear models [15]. In addition, decision trees are widely used for solving classification problems.…”
Section: Cost Estimation Techniquesmentioning
confidence: 99%